Analysis of Sales Information System (case Study: Mr. Token) - Agnes Fridawati; Wiwiet Herulambang; Arif Arizal (JEECS (Journal of Electrical Engineering and Computer Sciences), 2019)
At present the marketing that is in Mr. The token is done manually which is come directly to Mr.Token tooffer the products offered. The purpose of this study the authors analyze and design a sales information system Mr.Tokens to increase sales. Appropriate title taken is the analysis of sales information systems on Mr. Token. With theoccurrence of these constraints, the author tries to analyze the database by observing the database design. The purposeof this thesis is the researcher wants to be able to analyze the database in the company Mr. Token. And from the resultsof this study the results achieved are saving time of 12.6% and increasing turnover of 19.2%